Oroxyloside A Overcomes Bone Marrow Microenvironment-Mediated Chronic Myelogenous Leukemia Resistance to Imatinib via Suppressing Hedgehog Pathway - Zhang, Xiaobo; Liu, Yicheng; Lu, Lu; Huang, Shaoliang; Ding, Youxiang; Zhang, Yi; Guo, Qinglong; Li, Zhiyu; Zhao, Li (Frontiers in Pharmacology, 2017)
Imatinib (IM), as first inhibitor of the oncogenic tyrosine kinase BCR-ABL, has been widely used to treat chronic myeloid leukemia (CML) for decades in clinic. However, resistance to imatinib usually occurs in CML patients. The bone marrow (BM), as the predominant microenvironment of CML, secretes an abundant amount of cytokines, which may contribute to drug resistance. In current study, we utilized in vitro K562 co-culture model with BM stroma to investigate IM resistance. As a result, co-culturing of K562 with BM stroma was sufficient to cause resistance to IM, which was accompanied with the activation of hedgehog (Hh) signaling pathway and upregulation of BCR-ABL as well as its downstream proteins like phosphorylated Akt, Bcl-xL and survivin, etc. On the other hand, oroxyloside A (OAG), a metabolite of oroxylin A from the root of Scutellaria baicalensis Georgi, which had low toxic effect on K562 cells, was able to sensitize K562 cells co-cultured with BM stroma to IM treatment in vitro and in vivo. We observed that OAG suppressed Hh pathway and subsequently nuclear translocation of GLI1, followed by downregulation of BCR-ABL and its downstream effectors, thus facilitating IM to induce apoptosis of K562 cells. Together, BM microenvironment rendered K562 cells drug resistance through activating Hh signaling, however OAG could overcome IM resistance of CML cells through inhibiting Hh-BCR-ABL axis in vitro and in vivo.